A review of waste heat recovery and Organic Rankine Cycles (ORC) in on-off highway vehicle Heavy Duty Diesel Engine applications. (November 2017) - Lion, Simone; Michos, Constantine N.; Vlaskos, Ioannis; Rouaud, Cedric; Taccani, Rodolfo
Abstract: Heavy Duty Diesel Engine (HDDE) are between the biggest contributors to CO2 emission and ambient pollution as they are the most widely used technology for commercial vehicles and ship propulsion applications, as well as, together with reciprocating gas engines, for small medium-size distributed stationary power generation. New emission legislations in the on and off highway sectors, such as for example EURO VI and Tier 4 final, regarding NOx and Particulate Matter (PM), are also becoming year by year more stringent. For these reasons, in the last years, concerns about further engine development and efficiency improvement are of primary importance and several technologies have been studied and implemented. This review is meant to give an overview of the Organic Rankine Cycle (ORC) technology to recover wasted thermal energy in Heavy Duty Diesel Engines (e.g. exhaust gas, EGR, coolant circuit, charge air cooling, oil circuit) with particular focus on vehicle applications for on and off highway sectors (e.g. long-haul trucks, earth-moving machines, agricultural tractors). In addition, multiple different engine operating profiles in terms of torque and speed are gathered and reported for a variety of typical vehicles, in order to characterize the best system design point for the chosen application.